Insecure In Adolescent : Study Literature - Shobur, Sherly (International Journal Scientific and Professional, 2022)
Background: Adolescents are a vulnerable group who often experience feelings of insecurity or insecurity. Insecurity can have a negative impact on the psychological and social well-being of adolescents, such as decreasing the quality of interpersonal relationships, decreasing academic performance, and the emergence of mental health problems such as depression and anxiety. Therefore, it is important to understand what factors influence the level of insecurity in adolescents and strategies that can help them overcome this insecurity. Objective: The aim of this literature study is to identify factors that influence the level of insecurity in adolescents and strategies that can help them overcome this insecurity. Method: The method used in this literature study is literature search from various sources, such as academic journals, books, and online articles. A literature search was carried out using keywords related to insecurity and youth. Results: This literature study is expected to provide a better understanding of what factors influence the level of insecurity in adolescents and strategies that can help them overcome this insecurity. The results of this literature study are also expected to provide suggestions for parents, teachers, and mental health professionals in helping adolescents overcome insecurity and improve their psychological and social well-being.